PENGEMBANGAN APLIKASI ANALISIS TATA KELOLA SISTEM INFORMASI AKADEMIK DENGAN MENGGUNAKAN COBIT FRAMEWORK - Fitra Nugraha; Nazori Agani (FKOM UNIKU, 2015)
AbstractThe development of information technology has developed so rapidly at this time. IT progress is made every user can access a variety of data and information needed to easily and quickly. Increasing the role of IT in the enterprise is happening right now in fact also followed by changes in the company's business processes. Development of business strategy has always been associated with the development of IT strategy. Concepts of Information Technology (IT) governance is how to manage the use of information technology disebuah organization. IT Governance incorporate good practices of planning and organizing, development and implementation, distribution and services, as well as performance monitoring information system to ensure that the information and technology that can support the goals and mission of the organization. One way to determine this is to conduct the audit of the system. Audits conducted in order to establish the current state, look for deficiencies and recommend improvements to the informations system more useful in supporting informations. Academic information system services are complete, accurate, current, complete, secure, consistent, timely and relevant is very important for the University Brass to create user loyalty, improve the effectiveness and efficiency of resource use. In order to improve the efficiency of operations and academic information system service quality to its users, Universitas Kuningan required to develop a good business strategy, one of them by utilizing advances in information technology. In this paper, COBIT (Control Objectives for Information and Related Technology) can be used as tools used to streamline the implementation of information systems in the enterprise. COBIT consists of four domains, namely Planning - Organization (PO), Acquistion - Implementation (AI), Delivery - Support (DS) and Monitor - Evaluate (ME). COBIT framework is used to develop and implement a model of information system audit with the aim to provide input and recommendations to the management company for improving the management of information systems in the future. This research aims to reveal the importance of information systems auditing at the Universitas Kuningan, and make application management audit questionnaire web-based information systems.Keywords: IT audit, information systems,questionnaire, COBIT, Planning-Organization, Acquistion-Implementation, Delivery-Support, Manage-Evaluate